EFFECT OF INVENTORY TURNOVER AND LIQUIDITY ON PROFIT IN PT SGEEDE SOLUSI TEKNOLOGI DECLINED CURRENTLY IN THE DECLINED STAGE - Ronald Wangdra; Syahril Effendi (Universitas Putera Batam, 2023)
This research aims to determine the impact of inventory turnover and liquidity on the earnings of PT Sgeede Solusi Teknologi from 2018 to 2022. The R Square test results of this study show that 20.8% of the profit can be explained by inventory turnover and liquidity variables, while the remaining 29.2% is explained by other variables not found in the study. The results of the t-test showed that the number of inventories - that < -table or -2.299 < -2.002 and 0.025 < 0.05 significant level, which means that partial inventory turnover has a significant negative effect on profit. Similarly, with the results of t-test of liquidity variable which is 3.159 and significant level of 0.001 <0.05. It means that inventory turnover has a significant negative effect on profit.